2015
DOI: 10.5455/msm.2015.27.4-114-117
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Vascular Access on the Adequacy of Dialysis and the Outcome of the Dialysis Treatment: One Center Experience

Abstract: Introduction:Chronic kidney disease (CKD) is a gradually reduction in glomerular filtration rate (GFR) caused by destruction of a large number of nephrons. Kidney failure is the final stage of CKD with GFR <15ml/min/1.73m2 or requiring dialysis. Patients must provide vascular access, which is also the “life line” and “Achilles heel” of hemodialysis treatment.Aim:The purpose of this research is to show the demographic structure of the hemodialysis center in Konjic, and also demonstrate the impact of vascular ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Kt/V value alone not enough to identify AVF dysfunction, however, and it is recommended to evaluate this parameter together with physical examination [2]. Optimum blood pump speed increases dialysis adequacy, decreases patient morbidity and mortality, and increases quality of life [34,35]. The KDOQI guidelines recommend monitoring changes in Kt/V ratio and target blood flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…Kt/V value alone not enough to identify AVF dysfunction, however, and it is recommended to evaluate this parameter together with physical examination [2]. Optimum blood pump speed increases dialysis adequacy, decreases patient morbidity and mortality, and increases quality of life [34,35]. The KDOQI guidelines recommend monitoring changes in Kt/V ratio and target blood flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…These complications are similar to previous reports. 6,[9][10][11][12][13][14][15][16][17] The complications reported by Mahakalkar et al in patients with AVF were oedema, infection, bleeding at operative site, ecchymosis at the operative site.14 However, Susan et al reported early complications as thrombus, haematoma, bleeding and wound infection, and late complications as thrombosis, pseudoaneurysm. 15 In another study, majority of patients with AVF had steal phenomenon and distal edema.…”
Section: Discussionmentioning
confidence: 99%
“…13 Another study reported most common complication in patient with AVF was thrombosis (30.5%). 6 Another study reported data of 96 patients with 104 femoral catheters used for 1 to 26 days. Infection was the major complication reported with double-lumen femoral vein catheters consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Като причина за по-ниските показатели при пациентите от II група се прие дисфункцията на катетъра -невъзможност за достигане стойност на дебита над 250 мл/мин (12,16,20). Това най-често е свързано с неправилна позиция на РС непосредствено след поставянето му -прегъване на катетъра в подкожния тунел, а на по-късен етап във връзка с дислокация поради нарушена фиксация в областта на подкожния тунел -при по-дълги срокове на използване кожата изтънява, развиват се декубитуси и РС става нестабилен (2,6,22). В дългосрочен план дисфункцията на катетъра може да се предизвика и от интралуменни тромботични частици, тромбоза на РС поради неправилно запълване с хепаринизиран серум, усукване, пречупване на РС в областта на тунела (6,9,15,21).…”
Section: фиг 1 влияние на постоянния съдов достъп върху показателите ...unclassified